Simbolna krajina na širšem območju zgornje Vipavske dolineThe Symbolic Landscape in the Wider Area of the Upper Vipava Valley - Kompare, Tina (Studia mythologica Slavica, 2014)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The aim of the contribution is to reconstruct the symbolic landscape on the base of the folk tradition in the Upper Vipava Valley and surroundings. However, there are visible differences in observed elements between the valley and the plateau, which is the result of the duration of its being inhabited and the density of population. It is to be understood from the folk tradition that the Nanos plateau has been considered as a holy mountain before the arrival of Christianity.